Determinants of active aging and quality of life among older adults: systematic review - Marzo, Roy Rillera; Khanal, Praval; Shrestha, Sunil; Mohan, Devi; Myint, Phyo K.; Su, Tin Tin (Frontiers in Public Health, 2023)
ABSTRACT Introduction: Population demography across the globe shows an increasing trend in the ageing population due to better health care, improved nutrition, advanced health-related technology and decreased fertility rate. Despite these advancements, there remains a knowledge gap in understanding the association between active aging determinants and quality of life (QoL) among older adults, particularly within diverse cultural contexts, which has not been adequately explored in previous research. So, understanding the association between active ageing determinants and QoL can help policymakers plan early interventions or programs to assist future older adults in both ageing actively and optimizing their quality of life (QoL), as these two factors have a bidirectional relationship. Objective To review evidence regarding the association of active ageing and quality of life (QoL) among older adults and to determine the mostly widely used study designs and measurement instruments in studies conducted between 2000 and 2020 Methods Relevant studies were identified by a systematic search from four electronic databases and cross-reference lists. Original studies examining the association between active ageing and QoL in individuals aged 60 years or older were considered. The quality of the included studies, the direction and consistency of the association between active ageing and QoL were assessed. Results: Total of 26 studies met the inclusion criteria and were included in this systematic review. Most studies reported a positive association between active ageing and QoL among older adults. Active ageing had a consistent association with various QoL domains including physical environment, health and social services, social environment, economic, personal, and behavioral determinants. Conclusion Active ageing had a positive and consistent association with several QoL domains among older adults, backing the notion that the better the active ageing determinants, the better the QoL among the older adults. Considering the broader literature, it is necessary to facilitate and encourage the active participation of older adults in physical, social and economic activities for the maintenance and/or improvement of QoL. Identifying other possible determinants and enhancing the methods to improve those determinants may help improve the QoL among the older adults.